2016
DOI: 10.22159/ijpps.2016v8i12.13695
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Lipid Profiles Exhibited Among the Diabetic Asian Indians of India and Trinidad–a Comparative Study

Abstract: Objective: This was an cross-sectional observational study wherein clinical parameters were compared between the population of two countries like India and Trinidad. Methods:One hundred and six diabetic and 100 healthy individuals from Dakshina Kannada District of India were chosen and compared with 106 Type 2 diabetic and 100 healthy individuals of Trinidad. Along with anthropometric variables and blood pressure, blood samples were collected from the subjects aged above 35years of both genders who would fit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Diabetic children also have elevated lipid profile (TG, LDL, and cholesterol) and BP (SBP, and DBP) compared to controls. These results coincide with the previous data which proved that BP and lipid profile are elevated in diabetic children with the presence of positive correlation between DBP with diabetes duration and HbA1c levels [24][25][26]. The possible relationship between these factors and urinary 8-oxodG had been discussed in only a few studies.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetic children also have elevated lipid profile (TG, LDL, and cholesterol) and BP (SBP, and DBP) compared to controls. These results coincide with the previous data which proved that BP and lipid profile are elevated in diabetic children with the presence of positive correlation between DBP with diabetes duration and HbA1c levels [24][25][26]. The possible relationship between these factors and urinary 8-oxodG had been discussed in only a few studies.…”
Section: Discussionsupporting
confidence: 90%
“…Another study carried out among rural elderly in China reported the similar prevalence of high cholesterol (18.13%), while prevalence of high triglyceride (12.21%), low HDL cholesterol (32.76%), and high LDL cholesterol (13.23%) was lower compared to our findings [9]. Asian Indians have an abnormal fat distribution which makes it more prone to dyslipidemia [10].…”
Section: Discussionsupporting
confidence: 53%
“…Trend analysis of over two decades using data of two representative cross-sectional surveys conducted among men and women aged 35-64 years, residing in urban and rural areas (survey 1 [1991][1992][1993][1994], and survey 2 [2010][2011][2012]) in the National Capital Region of Delhi indicated that rapid rise in the burden of risk factors such as overweight, raised blood pressure, and raised blood glucose [12]. Indian diabetic population is also reported to have lower HDL-C and higher LDL [13].…”
Section: Discussionmentioning
confidence: 99%